Decarbonization and Decolonization of the Academy: A South-North Perspective - García, Magdalena (ACME, 2024)
This article invites reflection on possible paths toward a more equitable way of conducting research, which involve both decarbonizing academia and decolonizing knowledge production. Drawing on the work of Hopkins, I explore how academic travel perpetuates colonialist and capitalist power structures, often marginalizing scholars from the Majority World. In this vein, I propose four strategies to foster just geographies of knowledge, including prioritizing North-South articulation with the Majority World, promoting multilingualism, advocating for the redistribution of resources and recognition of locally produced academic knowledge, as well as exploring the potential of virtual conferencing as spaces where multilingual and multi-location dialogue can be embraced. Ultimately, I posit that embracing a more equitable approach to research serves as a pathway to decarbonizing academia.